Educational Management Strategies of Rajabhat University for the Consistency in Social Requirements - Donviset, Thanwadee (Journal for Developing the Social and Community, 2019)
The purposes of this research were to : 1) study educational management conditions of Rajabhat University, 2) study the social requirements towards educational management of Rajabhat University and 3) propose the educational management strategies of Rajabhat University that were consistent with the social requirements. This study utilized a mixed methods research. There were 768 of questionnaire respondents. The in-depth interview was used with 45 key informants. Data analysis were content analysis, proposing strategies and making a draft having it examined by experts in focus group discussion. The results found that : The educational management conditions of Rajabhat University as a whole was at the high-level including arts and culture conservation, graduate production research and community services respectively The social requirements towards the educational management of Rajabhat University : 1) Graduate production including the development of local curriculum and integration of educational 2) Research including the establishment of the research networking between the universities and local organizations 3) Community services including the development of community service system towards local curriculum preparation 4) Arts and culture conservation including the integration of local wisdom into the educational management system of the universities Educational management strategies of Rajabhat university that were consistent with the social requirements consisted of four strategies : (1) the educational management for local stability, (2) the development of graduate ability towards the digital society, (3) the integration of community services, research and innovation for the improvement of quality of life and (4) the strengthening of educational management efficiency.